Characterizing the semidiurnal internal tide off Tasmania using glider data. Issue 5 (27th May 2015) - Boettger, Daniel; Robertson, Robin; Rainville, Luc
Abstract The spatial structure of the semidiurnal internal tide in the vicinity of Tasmania is characterized using temperature and salinity data from Seaglider and Slocum glider deployments. Wavelet analysis of isopycnal displacements measured by the gliders was used to isolate the semidiurnal internal tide, with a solid signal observed both to the east and to the south of Tasmania. The signal south of Tasmania was attributed to local forcing, while that to the east of Tasmania was found to have propagated from the south east to the north west—a result which supports previous studies indicating the presence of an internal tidal beam originating over the Macquarie Ridge, south of New Zealand. Displacement amplitudes were observed to be amplified in the vicinity of the continental slope, with the incoming tidal beam shown to be both reflected and scattered on the continental slope and shelf, and energy transferred to higher modes.